The role of institutions at the nexus of logistic performance and foreign direct investment in Asia - Keng Lin Soh; Wai Peng Wong; Chor Foon Tang (Asian Journal of Shipping and Logistics (AJSL), 2021)
Foreign Direct Investment (FDI) plays an important part in the economic growth of developing Asia and logistics capability is a crucial factor in FDI location choice. Till today, research investigating Logistics Performance (LP) and FDI in Asia are still lacking and rather inconclusive and not standardised. Using a total of 31 Asian countries covering 2007 through 2017, the study critically investigates the impact of LP on FDI using static panel regression method. The results demonstrate that while LP significantly impact FDI, there is a threshold effect of institutional quality in the LP-FDI relationship. Specifically, this paper found that the impact of LP on FDI varies across the perceived level of institutional quality i.e., the effect is positive only before certain threshold level of institutional quality, after which the effect of LP on FDI is reversed. This finding suggests that the LP-FDI nexus is contingent on the perceived level of institutional quality, thus supporting the idea that innovations (i.e., creativity and flexibility embedded within a sound institutional framework) is potent in delivering long-run LP-FDI development in Asia.
Keywords: 650; Asia; Foreign direct investment; Institutional quality; Logistics performance